2005
DOI: 10.1631/jzus.2005.b0731
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic properties and heavy metal contents of automobile emission particulates

Abstract: Abstract:Measurements of the magnetic properties and total contents of Cu, Cd, Pb and Fe in 30 automobile emission particulate samples indicated the presence of magnetic particles in them. The values of frequency dependent susceptibility (χ fd ) showed the absence of superparamagnetic (SP) grains in the samples. The IRM 20 mT (isothermal remanent magnetization at 20 mT) being linearly proportional to SIRM (saturation isothermal remanent magnetization) (R 2 =0.901), suggested that ferrimagnetic minerals were re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
21
1
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(24 citation statements)
references
References 13 publications
0
21
1
2
Order By: Relevance
“…Magnetic mapping in magnetism has been well accepted for investigating industrial and urban pollution in different environments, such as soils, rivers/streams and lakes, different vegetative habitats, and roads (e.g., Hunt et al, 1984;Hoffmann et al, 1999;Matzka and Maher, 1999;Petrovský and Ellwood, 1999;Jordanova et al, 2003;Amereih et al, 2005;Lu et al, 2005;Zhang et al, 2006;Kim et al, 2007;Chaparro et al, 2007;Maher et al, 2008). A considerable number of studies have indicated relationships between magnetic parameters and heavy metal concentrations based on a genetic relationship from simultaneous production of both particle sources (e.g., Beckwith et al, 1986;Georgeaud et al, 1997;Petrovský et al, 1998;Knab et al, 2001;Spiteri et al, 2005;Chaparro et al, 2006Chaparro et al, , 2008.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Magnetic mapping in magnetism has been well accepted for investigating industrial and urban pollution in different environments, such as soils, rivers/streams and lakes, different vegetative habitats, and roads (e.g., Hunt et al, 1984;Hoffmann et al, 1999;Matzka and Maher, 1999;Petrovský and Ellwood, 1999;Jordanova et al, 2003;Amereih et al, 2005;Lu et al, 2005;Zhang et al, 2006;Kim et al, 2007;Chaparro et al, 2007;Maher et al, 2008). A considerable number of studies have indicated relationships between magnetic parameters and heavy metal concentrations based on a genetic relationship from simultaneous production of both particle sources (e.g., Beckwith et al, 1986;Georgeaud et al, 1997;Petrovský et al, 1998;Knab et al, 2001;Spiteri et al, 2005;Chaparro et al, 2006Chaparro et al, , 2008.…”
Section: Introductionmentioning
confidence: 99%
“…Although there are magnetic mapping studies of traffic-related areas, most of them focussed on the influence of pollutants on nearby soils, vegetation and dust particles. There is a scarcity of rockmagnetic studies of primary sources, such as soot and material from exhaust pipes (AbdulRazzaq and Gautam, 2001;Lu et al, 2005), as well as from the brake lining system of vehicles. This information can be useful for future investigation on identifying different contamination sources from vehicles and their influence.…”
Section: Introductionmentioning
confidence: 99%
“…1b) with high traffic density of more than 120 vehicles per minute. Road dusts suffer directly the inputs of vehicle emissions which often contain a great amount of magnetite-like particles with abundant Cu, Fe, Pb, and Zn (Hoffmann et al 1999;Lu et al 2005;Lu and Bai 2006;Prajapati et al 2006;McIntosh et al 2007). Due to the railway running along the Guishan South Road, railway debris may be also expected to contribute fine magnetic particles to road dust (Moreno et al 2003;Urbat et al 2004).…”
Section: Sources Of the Magnetic Particles And Heavy Metalsmentioning
confidence: 99%
“…Consequently, this factor may be explained by road/railway traffic, which is evident from the presence of high content of Cu with a mean value of 64.8 mg/kg and Fe with a mean content of 3.78% in the dusts. Lu et al (2005) reported that the average concentrations of Cu and Fe in vehicle emission particulates are up to 95.83 mg/kg and 3.47%, respectively. Factor 3 contributes 13.93% of the total variance (Fig.…”
Section: Sources Of the Magnetic Particles And Heavy Metalsmentioning
confidence: 99%
“…Та-кож значущі коефіцієнти кореляції встановлено між еле-ментами геохімічної асоціації елементів Cu-Pb-Zn. Дана асоціація є типовою техногенною асоціацією, зокрема для автотранспортного забруднення [11,12], яке є домі-нуючим в Одесі. На карті-схемі розподілу показника накопичення за-бруднення PLI за елементами Cu, Pb і Zn (рис.…”
unclassified